COVID-19 Pandemic as a Change Agent in the Structure and Practice of Statistical Consulting Centers. Issue 2 (3rd April 2022) - Lee, Shing; Bagiella, Emilia; Vaughan, Roger; Govindarajulu, Usha; Christos, Paul; Esserman, Denise; Zhong, Hua; Kim, Mimi
Abstract: When New York City (NYC) became an epicenter of the COVID-19 pandemic in the spring of 2020, statistical consulting centers at academic medical institutions in the area were immediately inundated with requests from hospital leadership and researchers for methodological support to address different aspects of the outbreak. Statisticians suddenly had to pivot from their usual responsibilities to focus entirely on COVID-19 work, and consulting centers had to devise innovative strategies to restructure their workflow and develop new infrastructure to address the acute demand for support. As statisticians from seven NYC-area institutions, we share our experiences and lessons learned during the pandemic, with the hope that this will lead not only to better preparedness for future public health crises when the skills and expertise of statisticians are critically needed, but also to lasting improvements to the structure and practice of statistical consulting centers.